2021
DOI: 10.3390/ijms22157826
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mGluR5 in D1 Receptor-Expressing Neurons Improves Stress Coping

Abstract: The metabotropic glutamate receptor type 5 (mGluR5) has been proposed to play a crucial role in the selection and regulation of cognitive, affective, and emotional behaviors. However, the mechanisms by which these receptors mediate these effects remain largely unexplored. Here, we studied the role of mGluR5 located in D1 receptor-expressing (D1) neurons in the manifestation of different behavioral expressions. Mice with conditional knockout (cKO) of mGluR5 in D1 neurons (mGluR5D1 cKO) and littermate controls d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…It is possible that a reduced mGlu5 receptor signaling in the prefrontal cortex and ventral hippocampus is instrumental for a better coping to stress in control mice. Prof. Francesco Ferraguti and his associates have found that conditional knock-out of mGlu5 receptors in D1 receptor-expressing neurons in the amygdala, nucleus accumbens, and dorsal striatum enhances coping with escapable and inescapable stress in mice [ 37 ]. It will be interesting to examine whether the selective deletion of mGlu5 receptors in the prefrontal cortex and ventral hippocampus affects the response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a reduced mGlu5 receptor signaling in the prefrontal cortex and ventral hippocampus is instrumental for a better coping to stress in control mice. Prof. Francesco Ferraguti and his associates have found that conditional knock-out of mGlu5 receptors in D1 receptor-expressing neurons in the amygdala, nucleus accumbens, and dorsal striatum enhances coping with escapable and inescapable stress in mice [ 37 ]. It will be interesting to examine whether the selective deletion of mGlu5 receptors in the prefrontal cortex and ventral hippocampus affects the response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal stress models have also shown robust changes in mRNA and protein levels as well as gene methylation levels of mGlu 1 and mGlu 5 receptor subtypes expressed in the hippocampus of offspring rats that exhibit depression-like behavior ( Lin et al, 2018 ). Several studies leveraging genetic deletion or pharmacological manipulation of group I mGlu receptors subtypes have further substantiated the notion that these receptors may be viable targets for treating stress-related disorders ( Li et al, 2006 ; Shin et al, 2015 ; Zangrandi et al, 2021 ). For instance, mGlu 5 knockout mice or mice that received the mGlu 5 NAM, MTEP, displayed detriments in stress coping mechanisms ( Li et al, 2006 ; Shin et al, 2015 ; Zangrandi et al, 2021 ).…”
Section: Potential Of Allosteric Modulators Of Metabotropic Glutamate...mentioning
confidence: 99%
“…Several studies leveraging genetic deletion or pharmacological manipulation of group I mGlu receptors subtypes have further substantiated the notion that these receptors may be viable targets for treating stress-related disorders ( Li et al, 2006 ; Shin et al, 2015 ; Zangrandi et al, 2021 ). For instance, mGlu 5 knockout mice or mice that received the mGlu 5 NAM, MTEP, displayed detriments in stress coping mechanisms ( Li et al, 2006 ; Shin et al, 2015 ; Zangrandi et al, 2021 ). A recent study showed that mice with conditional knockout of mGlu 5 in dopamine receptor D 1 neurons demonstrated divergent coping mechanisms in response to acute escapable or inescapable stress compared with littermate controls, such that mGlu 5 conditional knockout mice showed enhanced active stress coping upon exposure to escapable stress task and higher levels of passive strategy in response to inescapable stress ( Zangrandi et al, 2021 ).…”
Section: Potential Of Allosteric Modulators Of Metabotropic Glutamate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Under the condition of inescapable stress, these mice adopted an enhanced passive coping strategy, whereas, under the condition of acute escapable stress, they adopted an enhanced active coping strategy. These findings provided insights into the role of mGluR5, D1 receptor-expressing neurons, and their functional integration as key mediators of behavioral response to stress [14].…”
mentioning
confidence: 92%